Identificación de sitios alostéricos en proteínas de Homo sapiens que interactúan con la molécula de ATP mediante la herramienta Deacon Active Site Profiler (DASP3) (2020)
Active proteins and allosteric sites are distinguished in proteins. The latter have their binding site within the enzyme in a diﬀerent place from the active site. Its importance lies in the contribution it makes in the inhibition and / or activation of its biological function, this, through molecules (ligands) that act as allosteric modulators, being a basis for the design of drugs, since they provide fewer adverse eﬀects than traditional ones. (active regulators). One of the main molecules that can act as an allosteric regulator is adenosine triphosphate (ATP), since it is essential for obtaining cellular energy. Among the public databases that have information on the structure of proteins, is the National Center for Biotechnology Information (NCBI), there are 1,364,990 proteins in Homo sapiens, some of which have not been studied and therefore it is not known if there is an allosteric site, nor its molecular position. In the work that follows, the creation of an allosteric site proﬁle (ASP) is presented, from three proteins and with the help of the Deacon Active Site Proﬁler 3 tool (DASP3), which allows identify active sites by creating an active site proﬁle; these proteins, through the reviewed literature, are known allosteric site in interaction with the ATP ligand.